2011
DOI: 10.1523/jneurosci.0908-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Competition for Visual Selection in the Oculomotor System

Abstract: During behavior, the oculomotor system is tasked with selecting objects from an ever-changing visual field and guiding eye movements to these locations. The attentional priority given to visual targets during selection can be strongly influenced by external stimulus properties or internal goals based on previous experience. Although these exogenous and endogenous drivers of selection are known to operate across partially overlapping time scales, the form of their interaction over time remains poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…This approach was necessary here because subjects made relatively few fixations per trial. However, numerous studies have shown that initial fixations may differ from later fixations during visual search tasks (8,51,52) and free viewing (53). One difference between this task and other similar tasks is that we used a grayscale mask to enforce a specific viewing time (2 s).…”
Section: Discussionmentioning
confidence: 99%
“…This approach was necessary here because subjects made relatively few fixations per trial. However, numerous studies have shown that initial fixations may differ from later fixations during visual search tasks (8,51,52) and free viewing (53). One difference between this task and other similar tasks is that we used a grayscale mask to enforce a specific viewing time (2 s).…”
Section: Discussionmentioning
confidence: 99%
“…However, because the results for saccadic choices and for manual reactions were the same, it is likely that the results of these experiments depend mostly on the final state of the integration process. Markowitz et al (16) did measure the time course of how value and salience information compete for visual selection. Monkey observers had to choose between two targets that were defined by congruent or incongruent salience and reward information.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these experiments indicate that value can be an important determinant of the neural activity underlying the selection of a saccadic target when one object bears a higher reward than another (12)(13)(14)(15)(16). In these studies, a monkey observer typically selects between two or more spatially and visually distinct response alternatives that are associated with different rewards.…”
mentioning
confidence: 97%
“…Saccadic target selection is determined in part by the reward value of potential targets (1)(2)(3). Given the clear role of the FEF in target selection, it is surprising that few studies have explored the contribution of FEF dopamine to this behavior.…”
Section: Discussionmentioning
confidence: 99%